2010
DOI: 10.1177/1368430209355651
|View full text |Cite
|
Sign up to set email alerts
|

How should intergroup contact be structured to reduce bias among majority and minority group children?

Abstract: This experiment examined the effectiveness of one-group and dual-identity recategorization strategies on reducing intergroup bias among 180 European Portuguese and African Portuguese 9- and 10-year-old children. Results revealed that each of these recategorization strategies, relative to one that emphasized separate group identities, was successful in producing positive attitudes toward the outgroup children present during the session, the outgroup as a whole, and the outgroup as a whole three weeks later. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 47 publications
2
76
0
3
Order By: Relevance
“…For example, in contrast to the United States and United Kingdom, Portugal began to experience significant immigration only 40 years ago. Perhaps because of these immigrants' insecurity regarding their status, Guerra et al (2010) found a pattern opposite that typically controlled, F(1, 473) = 4.09, p = .044, η p = .01.…”
mentioning
confidence: 72%
“…For example, in contrast to the United States and United Kingdom, Portugal began to experience significant immigration only 40 years ago. Perhaps because of these immigrants' insecurity regarding their status, Guerra et al (2010) found a pattern opposite that typically controlled, F(1, 473) = 4.09, p = .044, η p = .01.…”
mentioning
confidence: 72%
“…Despite the impressive amount of studies that demonstrate the effectiveness of these two approaches, evidence supporting their basic predictions within educational settings is scarce (for exceptions, see e.g. Guerra et al, 2010;Vezzali, Capozza, Giovannini, et al, 2012). Second, our research contributes to the literature with regard to the underlying processes of the effects of imagined contact.…”
Section: Discussionmentioning
confidence: 99%
“…Support for the CIIM (Gaertner & Dovidio, 2000) has also been obtained among young children (Guerra et al, 2010;Houlette et al, 2004). For instance, Guerra and collaborators (2010) conducted an experimental intervention with majority (European-Portuguese) and minority (African-Portuguese) elementary school children in Portugal.…”
Section: Intergroup Contact and Common Ingroup Identitymentioning
confidence: 99%
“…19 There is considerable evidence from nonmedical settings that this recategorization approach can improve how members of different groups view one another, 17,18 and increase feelings of trust and forgiveness between groups that have distrusted and disliked one another. [20][21][22] The present research investigated whether an intervention derived from the common ingroup model can improve race-based trust in racially discordant primary care medical interactions, and thus produce more positive medical consequences. Physicians and their patients were randomly assigned to either a common ingroup identity treatment condition or a control condition.…”
Section: Introductionmentioning
confidence: 99%